Чинники та соціально-економічні ефекти розвитку сільського зеленого туризму в Україні - Гальків, Л. І.; Килин, О. В. (Видавництво Львівської політехніки, 2015)
Розкрито об’єктивну природу відпочинкових подорожей за межі міст. Охарактеризовано специфіку формування попиту на послуги у сфері сільського туризму. Досліджено термінологічний апарат тематики відпочинку у сільській місцевості. Охарактеризовано підходи до трактування сільського зеленого туризму вітчизняними науковцями, на основі чого сформульовано авторську дефініцію цього поняття. Структуровано чинники активування сільського зеленого туризму в Україні. Обґрунтовано соціально-економічні наслідки розвитку зеленого туризму для сільських територій та для їх населення. За даними Державної служби статистики України оцінено показники діяльності вітчизняних фізичних осіб-підприємців у сфері сільського (зеленого) туризму. Окреслено перспективи розвитку сільського зеленого туризму в Україні. The objective nature of recreation tours outside the city is discussed in the article. Specifics of creating demand for services of green tourism are characterized. The terminology of recreation in the countryside is studied. Approaches to treating green tourism by domestic scientists are characterized. The author’s definition of this concept is formulated as "the form of recreation outside the urban environment, with corresponding resource potential and scope, the positive effects of which go beyond the rural areas." Green tourism contributes to preservation and development of human heritage, revitalization of agricultural activities, improvement of tourism infrastructure, preservation of Ukrainian ethnocultural identity and environmental awareness. It led to government support program for the development of green tourism in European countries. Factors of stimulating green tourism in Ukraine are distinguished (demand growth, reasonable prices, historical and ethnographic heritage, recreational resources, affordable housing, environmental cleanliness) alongside with the discouraging factors (political and economic instability, negligent legal support, low level of human, advertising and information support, insufficient infrastructure and communications). Socio-economic effects of green tourism in rural areas are defined (amplification of agricultural production, improvement of welfare settelments, diversification of management forms, stimulation of services development) and advantages for their population (increase of real incomes, employment increase, improvement of educational and cultural levels) are presented. According to the State Service Statistics of Ukraine in 2012-2013, performance of the domestic natural individual entrepreneurs in green tourism is estimated. It is shown that not only the costs but also the quantitative indicators have increased: the number of estates; their area; the number of overnight stays; average length of stays. Dislocation of businesses in green tourism expanded from 13 to 20 areas. However, decrease is observed in tourist flows, cost per person-day; utilization of estates capacity. It is shown that business in green tourism is mostly concentrated in recreational areas of Ukraine. Rising dynamics create supply on the green tourism market and the existence of blank sectors in this market indicates the green tourism development perspectives in Ukraine. The experience of European countries is presented concerning the following issues: tax incentives; common rural development and tourism against the background of financial support to the private sector; specialization in cuisine, wine tasting, ethnographic, pilgrim tours; employment of tourists in agriculture and others. To improve the business environment in green tourism in Ukraine it is necessary to improve the regulatory framework and ensure its agreement with the EU; improve the investment climate; expand foreign economic activity; promote the value of healthy living based on the principles of sustainable tourism; adapt international experience to local realities.
Factors and socio-economic effects of rural green tourism in Ukraine
Keywords: туризм; сільські території; сільський туризм; зелений туризм; перспективність розвитку сільського зеленого туризму; tourism; rural areas; rural tourism; green tourism; the future development of rural tourism